2009
DOI: 10.1017/s0967199408004875
|View full text |Cite
|
Sign up to set email alerts
|

A combined treatment with ethanol and 6-dimethylaminopurine is effective for the activation and further embryonic development of oocytes from Sprague-Dawley and Wistar rats

Abstract: In nuclear-transferred or round spermatid-injected oocytes, artificial activation is required for further development in mammals. Although strontium chloride is widely used as the reagent for inducing oocyte activation in mice, the optimal method for oocyte activation remains controversial in rats because ovulated rat oocytes are spontaneously activated in vitro before artificial activation is applied. In our previous study, we found that cytostatic factor activity, which is indispensable for arrest at the MII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…This is not unprecedented, since other protein kinase inhibitors have been shown to promote this developmental response. For example, a wide range of studies have shown that the general kinase inhibitor 6-dimethylaminopurine is an effective inducer of parthenogenesis in oocytes of many mammalian species, including mouse (Szllosi et al, 1993;Liu et al, 1997;Nakasaka et al, 2000), rat (Jiang et al, 2002;Sano et al, 2009), cat (Yin et al, 2007), rabbit (Liu et al, 2002), pig (Leal and Liu, 1998;Jilek et al, 2001), bovine (Winger et al, 1997;Liu et al, 1998), sheep (Loi et al, 1998;Choi et al, 2004;Alexander et al, 2006), goat (Ongeri and Krisher, 2001), camel (Wani, 2008), rhesus monkey (Mitalipov et al, 2001), and human (Nakagawa et al, 2001). This is due in large measure to interruption of maturation promoting factor (MPF) activity, which is required to maintain MII arrest and is regulated by mitogen-activated protein kinase (Fan and Sun, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This is not unprecedented, since other protein kinase inhibitors have been shown to promote this developmental response. For example, a wide range of studies have shown that the general kinase inhibitor 6-dimethylaminopurine is an effective inducer of parthenogenesis in oocytes of many mammalian species, including mouse (Szllosi et al, 1993;Liu et al, 1997;Nakasaka et al, 2000), rat (Jiang et al, 2002;Sano et al, 2009), cat (Yin et al, 2007), rabbit (Liu et al, 2002), pig (Leal and Liu, 1998;Jilek et al, 2001), bovine (Winger et al, 1997;Liu et al, 1998), sheep (Loi et al, 1998;Choi et al, 2004;Alexander et al, 2006), goat (Ongeri and Krisher, 2001), camel (Wani, 2008), rhesus monkey (Mitalipov et al, 2001), and human (Nakagawa et al, 2001). This is due in large measure to interruption of maturation promoting factor (MPF) activity, which is required to maintain MII arrest and is regulated by mitogen-activated protein kinase (Fan and Sun, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The oocytes were activated by the following protocol, and the survival and cleavage rates were evaluated at 0 and 24 h after artificial activation. Artificial activation was carried out by a combined treatment with ethanol and 6-dimethylaminopurine (6-DMAP) according to our previous report [32]. In brief, oocytes were put in a fertilization medium (modified Rat 1-cell Embryo Culture Medium (mR1ECM) containing 110 mM NaCl and 4 mg/ml bovine serum albumin (BSA) and omitting polyvinyl alcohol (PVA) [33]) supplemented with 7% (v/v) ethanol (Kanto Chemical, Tokyo, Japan) for 3 min.…”
mentioning
confidence: 99%